Recent advances on halohydrin dehalogenases—from enzyme identification to novel biocatalytic applications - Schallmey, Anett (Appl Microbiol Biotechnol, 2016)
Halohydrin dehalogenases are industrially relevant enzymes that catalyze the reversible dehalogenation of vicinal haloalcohols with formation of the corresponding epoxides. In the reverse reaction, also other negatively charged nucleophiles such as azide, cyanide, or nitrite are accepted besides halides to open the epoxide ring. Thus, novel C-N, C-C, or C-O bonds can be formed by halohydrin dehalogenases, which makes them attractive biocatalysts for the production of various β-substituted alcohols. Despite the fact that only five individual halohydrin dehalogenase enzyme sequences have been known until recently enabling their heterologous production, a large number of different biocatalytic applications have been reported using these enzymes. The recent characterization of specific sequence motifs has facilitated the identification of novel halohydrin dehalogenase sequences available in public databases and has largely increased the number of recombinantly available enzymes. These will help to extend the biocatalytic repertoire of this enzyme family and to foster novel biotechnological applications and developments in the future. This review gives a general overview on the halohydrin dehalogenase enzyme family and their biochemical properties and further focuses on recent developments in halohydrin dehalogenase biocatalysis and protein engineering. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-016-7750-y) contains supplementary material, which is available to authorized users.